KONTRIBUSI SINTESIS TASAWUF-TEOSOFIS AL-GHAZÄLÄª TERHADAP KONSTRUKSI TASAWUF SUNNI - Aswadi, Aswadi (TEOLOGIA, 2013)
Abstract: Sufism of al-GhazÄlÄ« patterned the osophist, an integration between the theological and philosophical Sufism. The dominance pattern of the osophical Sufism of al-GhazÄlÄ« emphasizes the mystical experience is spread through philosophical reasoning. The his study method departed from the truth of faith and test it through mystical experience method. The peak of his Sufism leads to various dimensions, and then described through the frame work of rational thinking. According to al-GhazÄlÄ«, the essential Marifat to be obtained through inspiration or nÅ«r who Allah enter into the hearts of people to recognize the nature of God and all His creation. The knowledge is obtained from marifat more true than the knowledge is acquired by the reason. Abstrak: Tasawuf al-GhazÄlÄ« bercorak teosofis, merupakan integrasi antara tasawuf teologis dan filosofis. Dominasi corak tasawuf teosofisal-GhazÄlÄ« lebih mengedepankan pengalaman sufistik yang dibentangkan melalui penalaran filosofis. Metode kajiannya berangkat dari kebenaran iman dan mengujinya melalui metode pengalaman sufistik. Puncak tasawufnya bermuara pada tataran maârifat dengan berbagai dimensinya, kemudian diuraikan melalui kerangka berpikir rasional. Maârifat yang hakiki menurut al-GhazÄlÄ« diperoleh melalui ilham atau nÅ«r yang dicampakkan Allah ke dalam qalb manusia untuk mengenali hakikat Allah dan segala ciptaan-Nya. Ilmu yang diperoleh dari maârifat lebih benar daripada ilmu yang diperoleh melalui akal. Keywords: maârifat, qalb, teosofis, filosofis, gnostik.